Ukuran Kantor Akuntan Publik, Ukuran Perusahaan, Pergantian Manajemen dan Pergantian Kantor Akuntan Publik - Agoes Suanthara, Putu; Ary Wirajaya, I Gde (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p08, 2021)
The purpose of this study was to determine the effect of the size of the Public Accounting Firm (KAP), the size of the company, and the change of management on KAP Substitution. Research conducted on infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange in 2014-2018. The sampling method used is purposive sampling technique and the number of samples chosen is 11 companies with 55 samples in 5 years. Data collected by accessing the IDX official website to get the sample company's annual report, analyzed using logistic regression. Based on the results, KAP size has a significant negative effect on the KAP turnover. Company size and management change variables have a positive and not significant effect on public accounting firm changes. Keywords: KAP Size; Company Size; Management Change; KAP Substitution.